THE INFLUENCE OF DASAWISMA EMPOWERMENT ATTITUDES AND BEHAVIORS OF COMPLEMENTARY FEEDING (MPASI) FROM Moringa oleifera IN CHILDREN UNDER TWO YEARS OLD - Mulyanti, Sri; Astuti, Athanasia Budi (Jurnal Jamu Kusuma, 2024)
The incidence of stunting in Indonesia is still quite high even though in 2022 it has dropped to 21.6%, but it is still higher than the WHO standard of 20%. Providing complementary food by paying attention to the type of material and processing is the right effort in preventing stunting. Moringa leaves as a type of vegetable with vitamins A, C, and B6, calcium, potassium, and iron can be an option as complementary foods for children under two years. Even so, complementary feeding made from Moringa leaves must be done properly so that the child gets optimal nutrition and can prevent stunting. Based on this statement, this study was conducted to determine the effectiveness of dasawisma assistance on the attitudes and behaviors of complementary feeding by moringa in children under 2 years old. This research design is a Quasy Experiment with a pretest-posttest design approach. Respondents of the study were 100 families with children under two years old who were randomly taken in 10 villages in the Karanganom Klaten Health Center area. Training effectiveness was analyzed with the Wilcoxon test. The results showed that homestead assistance had a significant effect on increasing the positive attitude of mothers/companions with children under two years (baduta) old in providing complementary food for children under two years old (Mean±SD = 63.67±10.88: mean different: -4.59; p= 0.01); increased MPASI behavior (Mean±SD = 17.52±1.39 increased from 15.89±4.46, and mean different values: -1.63; p = 0.009).